Hubungan Stres dan Kesejahteraan (Well-being) dengan Moderasi Kebersyukuran - Erlis Manita; Marty Mawarpury; Maya Khairani; Kartika Sari (Gadjah Mada Journal of Psychology (GamaJoP), 2019)
This study aimed to determine the correlation of stress and well-being with gratitude moderation in early adults in Aceh. The method of this research was carried out using a quantitative approach. This study involved 349 early adults (264 female, 85 male) with age range of 20-40 years (M = 22.20) selected through the nonprobability sampling method with incidental sampling techniques. Individual’s stress levels were measured using the Perceived Stress Scale, well-being was measured using the Warwick-Edinburgh Mental Well-being Scale, and gratitude was measured using the Skala Bersyukur Indonesia. Data were analyzed using moderated regression analysis to test the research hypothesis. The results showed that stress had a significant negative relationship to well-being (β1 = -0.788; p < 0.05), then gratitude was able to moderate the relationship of stress and well-being (β3 = 3.257; p < 0.05). This study showed that there was a correlation between stress and well-being with gratitude moderation. It meant that grateful people focus on things that are grateful for every day, so that the impact on low stress levels and can improve individual well-being.